Prevalence of Wound Infection following Elective Surgery and Their Antimicrobial Susceptibility Pattern - Siddiqi, Md Nurul Alam; Hossain, Md Towhid (Chittagong University Journal of Biological Sciences, 2025)
Wound Infection or Surgical site infection (SSI) is most reported healthcare-associated infection and common surgical complication. The emergence of multidrug resistant bacterial pathogens in hospitals is becoming a challenge for surgeons to treat hospital acquired infections. This study aimed to find the microorganisms responsible for SSI and their antibiotic susceptibility profile. This prospective cross sectional observational study was conducted among 92 patients. Among them, 75 (81.5%) were culture positive. Monomicrobial growth was seen in 67 samples while 8 samples showed polymicrobial growth. Staphylococcus aureus (26.5%) was the commonest organism followed by Escherichia coli (22.8%), Klebsiella pneumonia (18.0%), etc. Antimicrobial profile of gram positive isolates revealed maximum sensitivity to vancomycin, teicoplanin and linezolid, whereas among gram negative isolates meropenem, piperacillin-tazobactam, and amikacin were found to be most sensitive. As a result of these problems, routine surveillance for hospital acquired wound infections, including surgical wound infections, is recommended. Chittagong Univ. J. B. Sci. Vol. 13 (1&2): 7-11, 2025